In-line skating - Roberts, Ben. (New York : Barron's Educational Series, 1999)
Describes aggressive skating, skates, safety, how to get started, halfpipes, big ramps, grinding, and other tricks.
"First published for the United Kingdom, 1977 by Franklin Watts, London"--Colophon.
Includes index.
Keywords: In-line skating -- Juvenile literature